Feeling Gender : A Generational and Psychosocial Approach - Bjerrum Nielsen, Harriet (Basingstoke Springer Nature, 2017)
Gender Studies; Sociology of Family, Youth and Aging; Family
English
Keywords: Feminism & feminist theory; Child care & upbringing; Gender Studies; Sociology of Family, Youth and Aging; Family